Effect of combined hormonal and insulin therapy on the steroid hormone receptors and growth factors signalling in diabetic mice prostate - Favaro, Wagner J. [UNESP]; Cagnon, Valeria H. A. (Wiley-Blackwell, 2010)
P>Diabetes causes harmful effects on prostatic morphology and function. However, there still are doubts about the occurrence of various diseases in the prostate, as well as abnormal angiogenesis in relation to diabetes. Thus, the aim of this study was to correlate and quantify the level of the steroid hormone receptors and the angiogenic and antiangiogenic factors in non-obese diabetic mice (Nod) after combined hormonal and insulin therapy. Sixty mice were divided into six groups after 20 days of diabetes: the control group received 0.9% NaCl, as did the diabetic group. The diabetic-insulin group received insulin, the diabetic-testosterone group received testosterone cypionate, the diabetic-oestrogen group received 17 beta-oestradiol, and the diabetic-insulin-testosterone-oestrogen group received insulin, testosterone and oestrogen simultaneously. After 20 days, the ventral lobe was processed for immunocytochemical and hormonal analyses. The results showed that the lowest serum testosterone and androgen receptor levels were found in the diabetic group and the highest testosterone and androgen receptor levels in the diabetic-insulin-testosterone-oestrogen group. The serum oestrogen level and its receptor showed changes opposite to those of testosterone and its receptor. The endostatin reactivity was mainly decreased in diabetic mice. The greatest IGFR-1 and VEGF reactivities occurred in diabetic mice. Thus, diabetes led to the prostatic hormonal imbalance, affecting molecular dynamics and angiogenesis in this organ. Combined insulin and steroid hormone therapy partially restored the hormonal and angiogenic imbalance caused by diabetes.
Keywords: diabetes mellitus; endostatin; IGFR-1; insulin; steroid hormones; VEGF; ventral prostate